Peptoid Ligands That Bind Selectively To Phosphoproteins - Cai, Di (2011)
Synthetic equivalents of phosphoprotein-specific antibodies would be valuable reagents for biological research, since these antibodies can often be difficult to produce. Protein phosphorylation is thought to result in significant conformational changes in most substrate proteins. Therefore, one approach might be to simply screen combinatorial libraries for ligands to the phosphorylated state in the hope of isolating a ligand that binds to a pocket created by the conformational shift. In this study, we probe this strategy by screening a peptoid library for ligands to the phosphorylated form of the Brd4 transcriptional coactivator protein. We find that peptoids with high selectivity for binding to phopshorylated form of Brd4 can indeed be isolated in this screen. Moreover, these ligands do not bind promiscuously to other phospho-proteins. However, attempts to employ these reagents as antibody substitutes in an immunoaffinity purification-like application showed that they do not perform as well as bona fide antibodies and that significant optimization will be required. This study highlights the potential and current limitations of a naïve library screening strategy for phosphoprotein-specific antibody surrogates.